2008
DOI: 10.1128/jvi.01533-08
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Tacaribe Arenavirus Z-Protein Binding Sites on the L Protein Identified both Amino Acids within the Putative Polymerase Domain and a Region at the N Terminus of L That Are Critically Involved in Binding

Abstract: Tacaribe virus (TacV) is the prototype of the New World group of arenaviruses. The TacV genome encodes four proteins: the nucleoprotein (N), the glycoprotein precursor, the polymerase (L), and a RING finger protein (Z). Using a reverse genetics system, we demonstrated that TacV N and L are sufficient to drive transcription and replication mediated by TacV In the present study, we mapped the TacV Z-binding sites on the 2,210-amino-acid L polymerase. To that end, we performed deletion analysis and point mutation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
34
0
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 33 publications
1
34
0
4
Order By: Relevance
“…1 E and F). Z has been identified as a binding partner to both host and viral proteins (15)(16)(17)(18)(31)(32)(33)(34). However, by establishing an in vitro model system of arenavirus RNA synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1 E and F). Z has been identified as a binding partner to both host and viral proteins (15)(16)(17)(18)(31)(32)(33)(34). However, by establishing an in vitro model system of arenavirus RNA synthesis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Most recently, budding by Z has been shown to be enhanced in the presence of viral NP (16). Z has also been shown to interact with NP and L (11,14,17,31,38), but the specific determinants in Z that mediate these viral protein interactions have yet to be fully elucidated.…”
mentioning
confidence: 99%
“…Indeed, we previously demonstrated that the interaction of TCRV Z protein with two noncontiguous regions in the L polymerase inhibits viral RNA replication and transcription (23,52). Nevertheless, the precise molecular determinants in Z mediating its interaction with L have remained elusive.…”
mentioning
confidence: 99%